التوافق النفسي لدى عينة من المتفوقين دراسيا - بوسالم، الشيماء, سعد الله، إيمان (جامعة الوادي university of Eloued, 2020)
ملخص هدفت الدراسة إلى الكشف عن التوافق النفسي لدى عينة من المتفوقين دراسيا من تلاميذ السنة الأولى ثانوي ببعض ثانويات ولاية الوادي،وقد تم الاعتماد على المنهج الاستكشافي لأنه الأنسب لهذه الدراسة وتم اختيار العينة بطريقة قصدية حيث تم اختيارها من بعض ثانويات ولاية الوادي ليكون عددها (60) تلميذ وتلميذة من السنة الأولى ثانوي. واشتملت الأدوات المستخدمة في هذه الدراسة على مقياس التوافق النفسي لعطية محمود هنا الذي عدد بنوده 30 بند، وبعدها تم المعالجة الاحصائية عن طريق برنامج spss، أما الأساليب الإحصائية المعتمدة في هذه الدراسة فهي الانحراف المعياري وألفا كرونباخ، معامل الارتباط سبيرمان براون وجيتمان واختبار(ت) وقد توصلنا إلى النتائج التالية: - أن مستوى التوافق النفسي لدى التلاميذ المتفوقين دراسيا منخفض. - لا توجد فروق ذات دلالة احصائية في التوافق النفسي لدى المتفوقين دراسيا تعزى لمتغير الجنس. - عدم وجود فروق دالة إحصائيا في التوافق النفسي لدى المتفوقين دراسيا تبعا لمتغير التخصص. وتمت مناقشة نتائج اعتمادا على معلومات نظرية ودراسات سابقة كما ختمنا الدراسة بخلاصة وبعض الاقتراحات والتوصيات بالإضافة إلى قائمة المراجع والملاحق. Abstract The study aimed to uncover the psychological compatibility of a sample of high school students from the first-year of secondary school in some secondary schools in the state of El-oued. The exploratory approach was relied upon as it is the most appropriate for this study. The sample is self-selected and was selected from some secondary schools of El-oued to be (60) Students (male and female) from the first-year of secondary school. The tools used in this study including the psychological compatibility scale of Attia Mahmoud, whose items numbered 30 sections, then, statistical analysis were performed using SPSS software. The statistical methods adopted in this study are the standard deviation, Cronbach's alpha, Spearman Correlation Coefficient and the (T) test. We found the following results: - The level of psychological compatibility among students who have excelled in studies is low. - The gender is statistically insignificant in the psychological compatibility differences among outstanding students. - The specialization is statistically insignificant in the psychological compatibility differences among outstanding students. Results were discussed based on theoretical framework and previous studies. We concluded the study with a summary, suggestions and recommendations in addition to a list of references and appendices
(دراسة ميدانية على عينة من تلاميذ السنة الأولى ثانوي ببعض ثانويات ولاية الوادي)
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: التوافق النفسي، المتفوقين دراسيا; Compatibilité psychologique, excellence académique; Psychological compatibility, academic excellence